PERAN KOMPOSISI MEDIA TANAM DAN PUPUK KALIUM DALAM PENINGKATAN HASIL TANAMAN TOMAT (Lycopersicon esculentum Mill.) - Sumarwoto Sumarwoto; Mahalia Dwita Budiastuti; Maryana Maryana (Agroland: Jurnal Ilmu-ilmu Pertanian, 2011)
The experiment of applying several kinds of media compositions and doses of KCl fetilizer aimed to determine media composition and potassium doses best for tomato plant (Lycopersicon esculentum Mill.) growth and yield. This experiment was conducted on February until Juny 2011 at “Balai Benih Induk Hortikultura” farm (± 625 m above sea level), Ngipiksari, Kaliurang, Sleman, Yogyakarta. The experiment used a Completely Randomized Factorial Design with three replications. The first factor was kinds of planting media composition (v/v/v): M1 =soil:goat faeces:sand (1:1:1); M2= soil:goat faeces:sand (2:1:1); and M3= soil:goat faeces:sand (1:1:2). The second factor was doses of potassium: D1 = KCl 75 kg ha-1; D2 = KCl 100 kg ha-1; = KCl 125 kg ha-1; and D4 = KCl 150 kg ha-1. The results of experiment showed that there is significant interaction between media compositions and doses of potassium on plant dry weight, and fruit diameter and thick. The M2D3 treatment resulted in highest contens of vit. C while the M2D2 in sugar content. The M1D1, M2D3, M3D2, and M3D3 treatments produced better taste than the others. The vegetatif growth (plant height, flowering time and harvest time) was only significantly affected by the media composition while the fruit yield by potassium fertilizer in which largest yield was found in the D3 treatment (3.75 g plant-1).